Tafsir dan New Media Studi Tentang Ayat Iman Menurut Hanan Attaki - Aufa Dzakiyyah Rahmi; Faisal Faisal; Novizal Wendry (Jurnal Ulunnuha, 2022)
Hanan Attaki's interpretation of the verses of faith on Youtube is phenomenal. He made Youtube his interpretive idea so that it could become evidence of the development of interpretive media from using old media to becoming new media. Hanan's interpretation is very different, he can invite the younger generation to increase their faith in God by using the language of today's children. This can trigger Hanan's many YouTube subscribers. Until now, Hanan's subscribers have reached 2.3 million with 88 million viewers. The purpose of this study is to examine the interpretation of the verses of faith which Hanan uses as the basis for preaching. In addition, this research identifies Hanan's method of interpreting verses and elaborating on subscriber comments. This study uses a qualitative method. Data was obtained from Hanan's YouTube Channel and other related references. The data is classified and interpreted through content analysis. Based on these data, it was found that Hanan used Qs. Ar-Ra'du verse 28, Qs. At-Taubah verse 124. And Qs. Al-Ankabut verses 1-3 and Qs. Al-Baqarah verse 214 is understood by Hanan as a verse of faith. He understands the importance of the younger generation believing in Allah and will go through phases including the ibtila phase (test phase) and the tamkin (help) phase. This led to many positive responses from subscribers who found Hanan's interpretation very interesting. This reinforces Marshall McLuhan's media theory quoted from Roudlotul Jannah's research which says that interpreters will be accepted by the younger generation if they can adapt to technology